Multislice computed tomography of cicatricial stenosis of the larynx and trachea - A. I. Kryukov; E. A. Kirasirova; N. V. Lafutkina; R. F. Mamedov; N. R. Gogoreva; V. A. Ekaterinchev; R. A. Rezakov (Медицинский совет, 2013)
Cicatricial stenosis is caused by pathological processes in the larynx and trachea leading to a narrowing of the lumen and resulting respiratory failure [10]. One of the main causes of cicatricial stenosis of the larynx and trachea is long-term mechanical ventilation via endotracheal and tracheostomy tube [2, 3, 4, 6, 9, 11].